O patrimônio da posse : um estudo da arquitetura militar do Espírito Santo no período colonial - Prata, Maria Catharina Reis Queiroz (2010)
Defense policy pursued by the Portuguese during the early centuries of Portuguese occupation of America resulted in the construction of forts, blockhouses and batteries in much of this territory, particularly in its extensive coastline. This dissertation